Investigating the risk factors of vestibular dysfunction and the relationship with presbyacusis in Singapore. Issue 9 (4th August 2016) - Tan, J L; Tang, J; Lo, S; Yeak, S
Abstract: Objectives: This study aimed to determine the prevalence of vestibular dysfunction in the Singaporean elderly and its association with presbyacusis, age and other associated risk factors. Methods: A cross-sectional study was undertaken in a tertiary otorhinolaryngology department and the community. Healthy adults aged 40 years and above who participated in the institution's community presbyacusis screening programme were invited to participate. The main outcome measures including pure tone audiometry and vestibular assessment were obtained using a modified Clinical Test of Sensory Interaction on Balance. Results: The prevalence of vestibular dysfunction and presbyacusis in the study population of 216 participants was 30.1 per cent (95 per cent confidence interval, 24.0 to 36.2 per cent) and 55.6 per cent (95 per cent confidence interval, 49.0 to 62.2 per cent), respectively. The median age was 60 years (range, 40–86 years). The adjusted odds ratio for vestibular dysfunction increased by 6.2 per cent with every year of life ( p < 0.05), and by 3.14 times in the presence of presbyacusis ( p < 0.05). After adjusting for age and presbyacusis, diabetes ( n = 30), hypertension ( n = 85), hypercholesteraemia ( n = 75), cardiac disease ( n = 14), stroke ( n = 7) and smoking ( n = 55) were associated with an increased odds ratio for vestibular dysfunction which did not reach statistical significance ( p > 0.05). Conclusion: Vestibular dysfunction is independently associated with ageing and presbyacusis. Further research into the benefits of additional screening for vestibular dysfunction in elderly presbyacusis patients is warranted.